The toxic effects of Coleus barbatus B. on the different periods of pregnancy in rats - Almeida, FCG; Lemonica, I. P. (Elsevier B.V., 2000)
Extracts of Coleus bal barbatus B. have been used in folk medicine to interrupt pregnancy. In order to evaluate if this plant interferes with embryo implantation or with the normal development of the concepts, pregnant Wistar rats were treated with increasing doses (220, 440 and 880 mg/kg per day) of a hydroalcoholic extract of C. barbatus. The rats received the extract by gavage from days 0 to 5 of pregnancy (preimplantation period) or 6 to 15 (organogenic period). Control groups received distilled water during the same periods: the animals were killed at term for the evaluation of maternal and fetal parameters. The results showed that the treatment with 880 mg/kg per day of the extract of C. barbatus before embryo implantation caused delayed fetal development and an anti-implantation effect, which justifies the popular use of this extract with abortive purposes. After embryo implantation delayed development associated with maternal toxicity was observed in the fetuses of the group which received 880 mg/kg per day. (C) 2000 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: Coleus barbatus; embryotoxicity; anti-implantation effect; teratogenicity; medicinal plants